Perancangan Kawasan Pantai Puri Gading Yang Tanggap Terhadap Potensi Bencana Tsunami Di Kota Bandar Lampung - Afinda Sugara, Chelvin; Wilfritz Soaduon Panjaitan, Tigor; Rolalisasi, Andarita (Rifa'Institute, 2023)
One of the natural disasters that can occur in Indonesia is a tsunami caused by geological factors. Indonesia is an area located on the